Analisis Dampak Lalu Lintas Pembangunan Kawasan Real Estat PT Meditec Prima Land di Sukabumi - Fery Hendi Jaya; Rhisna Dewi Septyawati (Universitas Darul Ulum, 2026)
The development of a real estate area potentially generates additional traffic movements that may affect the performance of surrounding road networks. This study aimed to analyze the traffic impacts generated by the development of PT Meditec Prima Land Real Estate located on Cibadak–Cikidang–Pelabuhan Ratu Road, Pamuruyuan Village, Sukabumi Regency. The study was conducted to identify existing traffic conditions, predict traffic performance during the construction and operational phases, and formulate appropriate mitigation measures. The research employed primary data collection through field surveys including road inventory, traffic volume counting, and observation of transportation conditions around the study area. The collected data were analyzed using trip generation and attraction analysis, trip distribution, modal split, and traffic assignment approaches. The results indicated that the construction and operational activities of the real estate development potentially increased traffic volumes on nearby road segments and intersections. Traffic performance simulations under several scenarios showed that without proper handling measures, the increase in traffic flow could reduce the level of service of the road network in the future. Therefore, traffic management and engineering measures were recommended, including access management, provision of adequate parking facilities, scheduling of construction vehicle operations, and installation of road equipment and pedestrian facilities. The implementation of these measures was expected to minimize traffic impacts and maintain traffic safety and mobility in the surrounding area.